Extracting Functional and Non-Functional Requirements for E-learning Systems (The International Journal of Educational Sciences and Arts, 2023)
Extracting functional & non-functional requirements is a basic step in software development. The process of requirements engineering includes seven main activities Elicitation, Negotiation, Specification, Modeling, Verification & Validation, Management, and Traceability, this study focuses on requirements engineering in E-learning systems to be performed in all educational systems. Non-functional requirements are considered more critical than functional requirements because the non-functional requirements can affect all the systems and some of non-functional requirements may become functional requirements like security. So, hoping that this constructed study is going to help the developers of the system to understand the requirements to build E-learning systems, especially in higher educational institutions.
Keywords: Education Technology; E-learning Systems; Requirements Engineering; Educational Systems; Software Development